2016
DOI: 10.1016/j.apm.2015.09.051
|View full text |Cite
|
Sign up to set email alerts
|

A new direct design method of wind turbine airfoils and wind tunnel experiment

Abstract: A general parametric representation function (Shape Function) for wind turbine-dedicated airfoils based on Taylor high-order polynomial series is presented for the first time. The design space and shape control function of the airfoil have been studied. The objective of the high-performance WT (Wind Turbine) airfoils was to maximise the lift/drag ratio at the design angle of attack both in free and fixed transitions. The optimised mathematical model of the airfoils is built combing genetic algorithm and the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 14 publications
0
19
0
2
Order By: Relevance
“…A number of factors affect the operation of the wind power plant, and thus the amount of the energy produced by the plant [13][14][15]. Among them, we can isolate the impact of the structural parameters of the wind power plant [16][17][18][19][20]. wind turbine drive and control systems [21][22][23][24][25][26], materials of components of the wind turbines [27][28][29][30][31][32][33][34][35], climatic factors or seismic events associated with the location [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors affect the operation of the wind power plant, and thus the amount of the energy produced by the plant [13][14][15]. Among them, we can isolate the impact of the structural parameters of the wind power plant [16][17][18][19][20]. wind turbine drive and control systems [21][22][23][24][25][26], materials of components of the wind turbines [27][28][29][30][31][32][33][34][35], climatic factors or seismic events associated with the location [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…If the inverse transformation is used to an arbitrary airfoil, the curve in the Z plane will be nearly circular. Because of limited the length of the article, the relevant theoretical knowledge can be read in literature [9] and [10]. The coordinate data of an arbitrary airfoil in the ζ plane can be written as follows:…”
Section: Airfoils Functional Integrated Expressmentioning
confidence: 99%
“…It was concluded that this method is capable of finding efficient and optimum airfoils in fewer generations. Chen and Wang [9,10] presented a general integral expression of airfoils based on a generalized functional and Trajkovski conformal transformation. CQU-DTU (Chongqing University) and WT (Wind Turbine) series airfoils have been designed successively using a multi-disciplinary optimal method.…”
Section: Introductionmentioning
confidence: 99%
“…A surrogate model based either on the Kriging or the artificial neutral network was alternatively used in the literature. [11][12][13][14][15] The article proposes to utilize the second-order response surface model (RSM) to mimic the aerodynamic performance, and its applicability is validated using the aerodynamic optimization of the NACA63418 and the DU93-W-210 airfoils.…”
Section: Introductionmentioning
confidence: 99%